Analisis Momentum Idul Adha 2023 Terhadap Inflasi Dalam Perspektif Islam - Muhammad Rasyid Ridlo; Muh. Ahsan Kamil (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
The momentum of Eid al-Adha 2023 is a big momentum that has the potential to cause inflation naturally as a result of the large economic transactions that occur in the market and currency circulation which is quite significant on certain days. This also happened due to the large demand for an item at that moment. The Eid al-Adha 2023 holiday, which is expected to last for 3 days, has great potential to trigger factors that cause inflation. The purpose of this study is to analyze the moment of Eid al-Adha 2023 for inflation and find a solution based on an Islamic perspective. The analysis technique in this study used a qualitative descriptive analysis approach with a literature study method. The findings of this study are to maintain Indonesia's economic stability during the momentum of Eid al-Adha 2023, it is necessary to hold an al hisbah institution in order to oversee the running of the economy in the market (market operations) to avoid inflation that occurs naturally. In addition, inflation must be suppressed in the long term by improving morale, equitable distribution of income and wealth, and eliminating usury